إفريقيا وسؤال الهوية - حمد بوصبع د. أحميد (Aljameai, 2024)
المستخلص: يقدم سؤال الهوية إشكالية (الأنا والآخر) في المجتمعات الإفريقية التي تعرضت للغزو الاستعماري الأوروبي الذي استغل ثرواتها المعدنية، واستخدم الأفارقه عبيداً، وعمل على تقويض هويتهم الثقافية واستيعابهم تدريجياً في ثقافته الكولونيالية، مستهدفاً أهم مكونات الهوية اللغة والدين ومجمل العادات والتقاليد؛ وبما أن الهوية ترتبط ارتباطاً وثيقاً بالفضاء الجغرافي و التاريخ والموروث الثقافي المكون الأساسي للذاكرة الجمعية، فلجأ الأفارقه إلى الثقافة الشعبية المتمثله في العادات، والتقاليد لتمجيدها، والاحتماء بها من تهديدات الآخر؛ لكي تمنحهم مزيداً من الثقة بالهوية الوطنية التي لها قدرة على التفاعل، واستيعاب القيم الإنسانية النبيلة من خلال تراثها الثقافي العميق، وتستطيع تحقيق التوازن بينها وبين تقاليد وثقافات الهويات المختلفة، والمتميزة عنها. Abstract: The question of identity poses a dilemma (self and other) in African societies that underwent European colonial invasion, exploiting their mineral wealth, using Africans as slaves, and working to undermine their cultural identity. Africans gradually assimilated into colonial culture, targeting key identity components such as language, religion, customs, and traditions. Since identity is closely linked to geographical space, history, and the cultural heritage, which is the fundamental component of collective memory, Africans turned to popular culture represented by customs and traditions to glorify and seek refuge from threats. This was done to grant them more confidence in their national identity, capable of interacting and assimilating noble human values through their deep cultural heritage. They could achieve balance between their identity and the traditions of different, distinct identities.